Attempted Suicide Pact by Married couple: A Case Study - Risal, A. (Journal of Psychiatrists’ Association of Nepal, 2017)
Suicide pact or a double suicide refers to the joint, actively induced death of two individuals at approximately the same time by mutual consent. News regarding these incidents is often found in media though scarcely published in medical literature. We report a psychiatric case history of a couple who attempted a suicide pact.